Embedded computing a VLIW approach to architecture, compilers and tools - Fisher, Joseph A. (Morgan Kaufmann, 2005)
The fact that there are more embedded computers than general-purpose computers and that we are impacted by hundreds of them every day is no longer news. What is news is that their increasing performance requirements, complexity and capabilities demand a new approach to their design. Fisher, Faraboschi, and Young describe a new age of embedded computing design, in which the processor is central, making the approach radically distinct from contemporary practices of embedded systems design. They demonstrate why it is essential to take a computing-centric and system-design approach to the traditional elements of nonprogrammable components, peripherals, interconnects and buses. These elements must be unified in a system design with high-performance processor architectures, microarchitectures and compilers, and with the compilation tools, debuggers and simulators needed for application development. In this landmark text, the authors apply their expertise in highly interdisciplinary hardware/software development and VLIW processors to illustrate this change in embedded computing. VLIW architectures have long been a popular choice in embedded systems design, and while VLIW is a running theme throughout the book, embedded computing is the core topic. Embedded Computing examines both in a book filled with fact and opinion based on the authors many years of R & D experience. Complemented by a unique, professional-quality embedded tool-chain on the authors' website, http://www.vliw.org/book Combines technical depth with real-world experience Comprehensively explains the differences between general purpose computing systems and embedded systems at the hardware, software, tools and operating system levels. Uses concrete examples to explain and motivate the trade-offs.